Analysis of Market System Mapping Patterns and Potential for Milkfish Cultivation in Pangkahwetan Village, Gresik Indonesia - Fadjar, Nurman Setiawan; Putri, Risqi Noor Hidayati (International Journal of Applied Business and International Management, 2024)
One of the potential resources in Indonesian villages is in the fisheries sector, which are divided into two main categories: capture fisheries and aquaculture. One of the common species for aquaculture in Indonesia is milkfish (chanos chanos). Pangkah Wetan Village in Gresik Regency is one of the areas that has the potential or value for milkfish aquaculture, which is influenced by the majority of the population who have a livelihood in the fisheries sector and because milkfish is relatively easy to cultivate due to its fast growth. In order to explore the potential for milkfish aquaculture, this research was carried out through an analysis of the market system approach. The productivity of milkfish aquaculture is determined by the optimization of its support functions. It was discovered that the cause of the low productivity of milkfish aquaculture was due to limitations in supporting services, not in the actors. The basic causes of this productivity include various seedlings quality, limited artificial feed, low utilization of technology, low access to capital, low marketing levels, and the minimal role of related institutions. Hence systemic intervention is necessary in terms of support services in order to improve the welfare of the community which in turn will increase the income of farmers.